Treatment for Preventing Tuberculosis in Children and Adolescents - Margarita E. Villarino; Nigel Scott; Stephen E. Weis; Marc Weiner; Marcus Barreto Conde; Brenda Jones; Sharon Nachman; Ricardo Oliveira; Ruth N. Moro; Nong Shang; Stefan Goldberg; Timothy R. Sterling (2015)
Importance Three months of a once-weekly combination of rifapentine and isoniazid for treatment of latent tuberculosis infection is safe and effective for persons 12 years or older. Published data for children are limited. Objectives To compare treatment safety and assess noninferiority treatment effectiveness of combination therapy with rifapentine and isoniazid vs 9 months of isoniazid treatment for latent tuberculosis infection in children. Design, Setting, and Participants A pediatric cohort nested within a randomized, open-label clinical trial conducted from June 11, 2001, through December 17, 2010, with follow-up through September 5, 2013, in 29 study sites in the United States, Canada, Brazil, Hong Kong (China), and Spain. Participants were children (aged 2-17 years) who were eligible for treatment of latent tuberculosis infection. Interventions Twelve once-weekly doses of the combination drugs, given with supervision by a health care professional, for 3 months vs 270 daily doses of isoniazid, without supervision by a health care professional, for 9 months. Main Outcomes and Measures We compared rates of treatment discontinuation because of adverse events (AEs), toxicity grades 1 to 4, and deaths from any cause. The equivalence margin for the comparison of AE-related discontinuation rates was 5%. Tuberculosis disease diagnosed within 33 months of enrollment was the main end point for testing effectiveness. The noninferiority margin was 0.75%. Results Of 1058 children enrolled, 905 were eligible for evaluation of effectiveness. Of 471 in the combination-therapy group, 415 (88.1%) completed treatment vs 351 of 434 (80.9%) in the isoniazid-only group (P = .003). The 95% CI for the difference in rates of discontinuation attributed to an AE was −2.6 to 0.1, which was within the equivalence range. In the safety population, 3 of 539 participants (0.6%) who took the combination drugs had a grade 3 AE vs 1 of 493 (0.2%) who received isoniazid only. Neither arm had any hepatotoxicity, grade 4 AEs, or treatment-attributed death. None of the 471 in the combination-therapy group developed tuberculosis vs 3 of 434 (cumulative rate, 0.74%) in the isoniazid-only group, for a difference of −0.74% and an upper bound of the 95% CI of the difference of +0.32%, which met the noninferiority criterion. Conclusions and Relevance Treatment with the combination of rifapentine and isoniazid was as effective as isoniazid-only treatment for the prevention of tuberculosis in children aged 2 to 17 years. The combination-therapy group had a higher treatment completion rate than did the isoniazid-only group and was safe. Trial Registration clinicaltrials.gov Identifier:NCT00023452